Global burden of rabies in 204 countries and territories, from 1990 to 2019: results from the Global Burden of Disease Study 2019. (January 2023) - Gan, Hui; Hou, Xiangqing; Wang, Yiming; Xu, Gaofeng; Huang, Zhifeng; Zhang, Teng; Lin, Runpei; Xue, Mingshan; Hu, Haisheng; Liu, Mingtao; Cheng, Zhangkai J.; Zhu, Zheng; et al.
Highlights: Rabies deaths were 13, 743.44 (95% uncertainty interval: 6019.13-17, 938.53) in 2019. The global disease burden of rabies had declined over the past 30 years. The disease burden of rabies was closely related to the sociodemographic index level. Abstract : Objectives: Rabies is an acute lethal infectious disease caused by a lyssavirus infection. In 2018, the World Health Organization proposed a global strategic plan to end human rabies deaths by 2030. However, systematic studies on the global rabies disease burden and epidemiological trends are scarce. Methods: We extracted the disease burden and epidemiological data of rabies worldwide in the preceding 30 years from the Global Burden of Disease Study 2019 and performed a comprehensive analysis. Results: In 2019, the incident cases of rabies worldwide were 14, 075.51 (95% uncertainty interval: 6124.33-21, 618.11), and the number of deaths was 13, 743.44 (95% uncertainty interval: 6019.13-17, 938.53), both of which were lower than that in 1990. With the improvement of the sociodemographic index, the incident cases, the number of deaths, age-standardized incidence rate, age-standardized incidence death rate, and disability-adjusted life years of rabies all showed downward trends. Adolescents and adults aged <50 years represented the majority of rabies cases worldwide. Conclusion: The global disease burden of rabies has declined over the past 30 years. Furthermore, the disease burden of rabies was closely related to the sociodemographic index level.